HTML5 Geolocation - Holdener, Anthony T. (O'Reilly, 2011)
Truly revolutionary: now you can write geolocation applications directly in the browser, rather than develop native apps for particular devices. This concise book demonstrates the W3C Geolocation API in action, with code and examples to help you build HTML5 apps using the "write once, deploy everywhere" model. Along the way, you get a crash course in geolocation, browser support, and ways to integrate the API with common geo tools like Google Maps. Learn how geo information is gathered from different sources, depending on the deviceDiscover how coordinate systems work, including geodetic system.